Determination of Vanadium(V) by Kinetic-Catalytic Spectrophotometric Method Using the Oxidation of Commassive Violet R 150 by Bromate - Keyvanfard, Mohsen (Asian Journal of Chemistry, 2010)
A new, simple, sensitive and selective catalytic spectrophotometric method was developed for the determination of trace amounts of vanadium(V). The method is based on the catalytic effect of vanadium(V) on the oxidation of commassive violet R150 by bromate in acidic medium. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of commassive violet R150 at 632 nm with a fixed-time method. The decrease in the absorbance of commassive violet R150 is proportional to the concentration of vanadium(V) in concentration range 20-300 ng/mL, with a fixed time of 0.5-2.0 min from initiation of the reaction. The limit of detection is 8 ng/mL vanadium(V). The relative standard deviation of 100 and 200 ng/mL vanadium(V) was 2.6 and 2.8 %, respectively. The method was applied to the determi-nation of vanadium(V) in natural water.